Prevalence and Associated Factors of Suicidal Behavior Among Patients and Residents in Northwest Ethiopia - Belete, Habte; Misgan, Eyaya; Belete, Tilahun (Frontiers in Psychiatry, 2021)
There are a million suicide deaths in the world annually, and 75% of these occur in low- and middle-income countries (LMICs). However, there are limited resources to prevent suicidal deaths in those regions. The aim was to assess the prevalence of suicidal behavior and associated factors among patients visiting for medical care at a health center and residents in the community. A comparative study was employed by interviewing 2,625 residents in the community and 1,363 patients at the health center about suicidal behavior in northwest Ethiopia, from March 2017 to February 2018. Logistic analysis was employed with adjusted odds ratios and 95% confidence interval (CI) and with p-value < 0.05. The total prevalence of suicidal behavior (ideation, plan, and attempt) was found to be 5.6% (with 95% CI range 5–6%). It was found to be 4.4% with 95% CI range 4–5% in residents and 7.9% with 95% CI range 6–9% in patients. Female sex, depressive symptoms, physical/verbal abuse, and feeling stigmatized were identified as a risk factors for suicidal behavior, whereas a healthy lifestyle, such as eating regular meals of fruits and vegetables, doing physical exercise regularly, and having public health insurance were identified as protective risk factors for suicidal behavior even after adjusting for being a patient or not. The proportion of suicidal behavior was double in patients compared with residents. Suicidal behavior should be assessed in patients who visit for medical help and integration of mental health service within the primary health care system is recommended, especially in low-income countries.